The Influence of Interest in Learning on Learning Achievement in Economics Subjects of Class XI IPS Students at SMA Negeri 6 Pekanbaru - Bhayu Utama Putra; Gusnardi Gusnardi; Filma Alia Sari (CV. Rayyan Dwi Bharata, 2024)
This research aims to determine the influence of interest in learning on learning achievement in economics subject for class XI IPS students at SMA Negeri 6 Pekanbaru. Achievement of learning achievement must be achieved, namely achieving minimum completeness criteria. The better the students learning achievement, the better the quality of the individual. A situation that attracts students attention is expected to arouse students interest in learning. Students interest in learning usually results in high achievement, working based on their abilities in each lesson. Economics lessons that students consider boring are givent attention as well as learning materials that attract students interest. The number of samples in this study was 85 people, the sampling technique used simple random sampling method. The data analysis technique used in this research is simple linear regression. The measurement results for student interest in learning are in the high category, namely 55,3%, this is because students are enthusiastic in participating in the learning process so that students are able to understand the learning being delivered, listen and pay attention to the teacher explanation so that it attracts students assumptions that material being taught is interesting and not boring, and plays an active role in learning, causing high curiosity and assuming that the knowledge they have is still minimal regarding economic learning. The level of learning achievement in economics subjects obtained scores that were included in the quite good category, namely 35 people or 41.2%. This is slightly different from the frequency of learning based on the KKM, but it already meets the minimum completeness criteria (KKM). Judging from the calculation of the coefficient of determination (R2) 65% of the variation in changes in learning achievement that occurs can be explained by variations in changes in learning interest. Meanwhile, the remaining 35% is explained by other factors not included in this research such as learning facilities and learning motivation, teacher teaching skills and learning discipline.